2020
DOI: 10.1186/s40792-020-00998-4
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the transverse colon with lymph node metastasis and malignant transformation: a case report

Abstract: Background The concept of GIST was established in 1998, clearly differentiating between gastrointestinal leiomyosarcoma and GISTs among gastrointestinal mesenchymal tumors. Lymph node metastasis is extremely rare in true gastrointestinal leiomyosarcoma, and there are no reports of malignant transformation from leiomyoma. Case presentation The patient was an old woman who had undergone endoscopic mucosal resection for an Is polyp on the left side of the transverse colon at the age of 73. She was diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Metastasis mainly occurs haematogenously, most commonly to the lungs and liver, and is considered to be incurable; these patients are offered palliative treatment. Metastasis to lymph nodes is extremely rare in true GI LMS, but not considered to be incurable as is the case for distant haematogenous metastasis 12–14. To date, no similar cases of intra-abdominal LMS have discussed the role of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis mainly occurs haematogenously, most commonly to the lungs and liver, and is considered to be incurable; these patients are offered palliative treatment. Metastasis to lymph nodes is extremely rare in true GI LMS, but not considered to be incurable as is the case for distant haematogenous metastasis 12–14. To date, no similar cases of intra-abdominal LMS have discussed the role of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that leiomyosarcoma areas harbored genetic alterations that were found in the corresponding leiomyoma-like areas, and in addition, leiomyosarcoma areas had additional genetic alterations including Myc amplification, loss of foci for RB-1, TP53, etc. Recently, Tago et al 16 reported a case of colonic leiomyosarcoma that highly likely developed through malignant transformation of leiomyoma which was endoscopically resected 3 years ago. This colonic case is the first report of malignant transformation of the gastrointestinal tract, and our gastric case is the first to demonstrate direct transition from leiomyoma to leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of preventive lymph node dissection is still controversial. Of all the reported cases on colonic LMS, only two cases have been shown to exhibit lymph node metastasis 15 16…”
Section: Discussionmentioning
confidence: 99%